2022
DOI: 10.1097/xcs.0000000000000472
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and Disease-Free Survival Outcomes after Hepatectomy for Centrally Located Hepatocellular Carcinoma Guided by Augmented Reality and Indocyanine Green Fluorescence Imaging: A Single-Center Experience

Abstract: BACKGROUND: Laparoscopic hepatectomy for centrally located hepatocellular carcinoma is challenging to perform. Augmented reality navigation (ARN) and fluorescence imaging are currently safe and reproducible techniques for hepatectomy, but the efficacy results for centrally located hepatocellular carcinoma have not been reported. This study aimed to evaluate the efficacy of an ARN system combined with fluorescence imaging (ARN-FI) in laparoscopic hepatectomy for centrally located hepatocellular carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The group found that the patients undergoing surgery with the combination of ARN and fluorescent imaging had significantly reduced intraoperative blood loss and transfusion rates, shorter postoperative length of stay, and lower perioperative complication rates when compared to patients undergoing routine laparoscopic hepatectomy. They also found that the combination of methods significantly reduced the rate of conversion to laparotomy (35.7% vs. 61.8%, p = 0.024) [91].…”
Section: Visualization Techniquesmentioning
confidence: 94%
See 3 more Smart Citations
“…The group found that the patients undergoing surgery with the combination of ARN and fluorescent imaging had significantly reduced intraoperative blood loss and transfusion rates, shorter postoperative length of stay, and lower perioperative complication rates when compared to patients undergoing routine laparoscopic hepatectomy. They also found that the combination of methods significantly reduced the rate of conversion to laparotomy (35.7% vs. 61.8%, p = 0.024) [91].…”
Section: Visualization Techniquesmentioning
confidence: 94%
“…This technique uses CT images to create a 3D reconstruction of the anatomy and can help to determine a tumor's resectability, as well as a surgical plan [90]. Recently, studies have explored the possibility of using 3D models in real time during surgery, an approach named augmented reality navigation (ARN) [91,92].…”
Section: Visualization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 1,919 studies were excluded due to duplication, and an additional 2,731 studies were removed after reviewing their titles and abstracts. The remaining 39 full-text articles were reviewed, followed by the removal of 28 articles for various reasons, resulting in the inclusion of 11 studies (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in the meta-analysis (Figure 1). All 11 studies were retrospective cohort studies, with nine conducted in China and the remaining two in Japan.…”
Section: Study Identification Quality and Baseline Characteristics Of...mentioning
confidence: 99%